Estimation of the place of the Russian Federation by specific weight in the total number of articles on clinical medicine, indexed in the Web of Science - N. G. Kurakova; L. A. Tsvetkova; O. V. Cherchenko (Ekonomika Nauki)
The place of the Russian Federationby specific weight in the total number of articles in the field of clinical medicine, indexed in the international database Web of Science Core Collection (WoS CC) is determined. It is shown that if you strictly comply with the wording of the target of the National Project “Science” and assume that correctly all publications on clinical medicine, indexed in WoS CC, refer to the priority “transition to personalized medicine, high-tech healthcare and health protection technologies, including the expense of rational use of drugs (primarily antibacterial “, then the basic value of this target should be defined as the 36th place in the world. For eniya Russian Federation, one of the five leading countries in the publication activity in the field of clinical medicine Russian professional medical community needs to increase by 13 times the number of articles indexed in the WoS CC, to surpass Japan’s figures, which occupies the 5th position at the end of 2017.